Cost-Benefit Analysis of Preventive Healthcare Programs - Mehboob, Khurram (Pakistan Journal of Health Sciences, 2025)
In an age where healthcare systems are burdened with rising costs and increasing demands, one truth remains constant: preventing disease is far less expensive—and more effective—than treating it. Preventive healthcare programs, often overshadowed by curative medicine, are a long-term investment with undeniable economic and social returns. Programs for health promotion have been heralded as having enormous potential to assist in addressing the issue of rapidly rising health care expenses. Program evaluation must include a cost-benefit or cost-effectiveness analysis to determine whether health promotion initiatives are "worth it." Preventive healthcare includes a wide range of interventions—regular screenings, vaccinations, smoking cessation programs, nutrition education, and early detection of diseases. These initiatives aim to catch health issues before they become severe and costly. And while the upfront costs of such programs can seem steep, the cost savings over time are substantial. Fewer hospital admissions, reduced need for expensive treatments, and minimized emergency room visits all translate into billions in savings for healthcare systems. All project-related expenses and benefits must be measured and converted into monetary values to determine the welfare change attributable to the project (i.e., the project's net benefit to society as a whole). In ex ante evaluation, policymakers utilize CBA as a tool to choose between different projects or determine whether a certain plan is beneficial to society. It can also be used ex post to calculate the net social value of a particular program that has been fully completed. Moreover, preventive care enhances health equity. Community-based initiatives, mobile screenings, and free vaccination clinics can bridge the gap for underserved populations, ensuring that everyone has access to the tools they need to stay healthy. Preventive care is not just an economic decision—it’s a public good. So, what should we do? Policymakers must prioritize funding for preventive services, insurers should cover them comprehensively, and public awareness campaigns should emphasize their importance. We must shift the conversation from curing disease to preventing it. Investing in preventive healthcare is investing in our collective future. The cost-benefit analysis isn’t just in the numbers—it’s in the healthier lives, stronger communities, and sustainable systems we build along the way. preventive care promotes a healthier, more productive population. When people are healthy, they can work, care for their families, contribute to the economy, and live longer, more fulfilling lives. Chronic illnesses like diabetes, heart disease, and certain cancers—many of which are preventable or manageable if caught early—account for a large portion of healthcare spending and productivity loss. Tackling them through prevention makes fiscal and moral sense.